UNDERPRICING PENGARUHNYA TERHADAP IPO AFTERMARKET LIQUIDITY - Nilmawati Nilmawati (Jurnal Keuangan dan Perbankan, 2009)
The purpose of the research was to analyze and fi nd empirical evidence of underpricing onIPO aftermarket liquidity in the listed companies in Indonesian Stock Exchange. Independent samplet-test and multiple linier regression were used for instrument analysis. Results showed that IPO aftermarketliquidity between fi rm with high underpricing and low underpricing were not different.The results also indicated that initial return was positively related to turnover ratio and negativelyrelated to percentage spread (weak effect) by controlling variables such as: size,volume,and risk inshort time.